On one generalization of Wronskian - Kirjackis, Eduardas (Lietuvos matematikos rinkinys, 2007)
In this article the properties of the specially introduced determinant, elements of which are the divided differences in different orders are studied. The close connection of this determinant with the Chebyshev system and the ordinary differential equation is indicated.